Modelling mobile attachment and cyber hygiene behavior of users - Dawie, Ferdinand Jilan; Masrek, Mohamad Noorman; Abdul Rahman, Safawi (Faculty of Information Management, 2025)
This research examines how mobile attachment relates to cyber hygiene behaviors among mobile phone users in Malaysia. We adopt Partial Least Squares Structural Equation Modelling (PLS-SEM) to analyze survey data, the study. The findings suggest that functional dependence and deep structure use positively impact cyber hygiene intentions, while mobile identity has no direct effect. Theoretically, the study extends attachment theory by linking functional dependence with proactive security behaviors. Limitations include cultural specificity and self-reported data, highlighting the need for future studies across diverse populations to explore additional influences on mobile attachment and security behaviors.